(untitled) (Journal of Engineering, 2021)
Collapsing building structures during recent earthquakes, especially in Northern and Eastern Kurdistan, including the 2003 earthquake in Cewlig; the 2011 earthquake in Van; and the 2017 earthquake near Halabja province, has raised several concerns about the safety of pre-seismic code buildings and emergency facilities in Erbil city. The seismic vulnerability assessment of the hospital buildings as emergency facilities is one of the necessities which have a critical role in the recovery period following earthquakes. This research aims to study in detail and to extend the present knowledge about the seismic vulnerability of the Rizgary public hospital building in Erbil city, which was constructed before releasing the seismic provisions in the region. ETABS software is employed to conduct Eigenvalue analyses, nonlinear static analyses, and about 120 incremental dynamic analyses; furthermore, the actual response of the hospital building is evaluated by considering possible irregularities in both directions and the effect of seismic pounding. The outcomes of the research indicate that the hospital building is in poor performance under anticipated earthquakes. In addition, the existing combination of irregularities and seismic pounding in the model increases the vulnerability under the seismic load. A suitable strengthening strategy is also recommended.